An overview of quality management system in construction - Mohammed, Abdul Hakim (Penerbit UTM, 2008)
The study on the QMS in construction industry would be difficult to proceed if the definition of the quality and the QMS are not well understood. Therefore, this chapter begins with the discussion on both subjects.